CAMINANDO HACIA LA PRIMERA ECOPOLITICA DE LA ALDEA GLOBAL - Alfaro Castellanos, Eduardo Luis (2022)
The research aims to show that Peru, in its southern zone, has enormous amounts of Solar Radiation, the same that belongs to Renewable Energies, which would allow us to see the immediate future with optimism, for the generation of wealth, start the change of the National Energy Matrix and the reduction of poverty prioritizing the attention of the National Development and Social Inclusion Policy, in its strategic axis "Pension 65", the same one that would be favored with a Basic Income that will be the product of a percentage of the generation of this inexhaustible source, daily and permanent. We will make a quick analysis of the Basic Income, of the models applied in the world and their results and we will thus see a new model, a new Policy, which we call, the "First Eco-Policy of the Global Village".